Unusual association of limbic encephalitis in pediatric pulmonary tuberculosis-a rare case report - Selvamani, Dhanraj; Singh, Tamanna Veer; Middha, Rahul; Mehra, Shibani (International Journal of Contemporary Pediatrics, 2024)
Limbic encephalitis is an inflammatory condition that is rarely associated with tuberculosis. The literature shows only three cases, and all of them were seen in adults. We reported a case of an 11-year-old female child who came for fever with altered sensorium and on evaluation, the diagnosis of limbic encephalitis associated with tuberculosis was made. The thought of tuberculosis infection has to be given while making the diagnosis of limbic encephalitis.